CAN GROUP RIGHTS JUSTIFY THE DENIAL OF EDUCATION TO ADOLESCENTS? THE AMISH IN THE UNITED STATES AS A CASE STUDY - Cohen-Almagor, Raphael (Revista Direitos Sociais e Políticas Públicas (UNIFAFIBE), 2025)
Multiculturalism gives preference to group rights over individual rights. This may challenge democratic values. This paper focuses on the Amish denial of education from their adolescents. Criticizing Wisconsin v. Yoder (1972), the paper analyses the power of the Amish community over its members. The main questions are: Is it reasonable to deny the Amish adolescents’ standard American education? What are the limits of state interference in norms of illiberal communities who invoke separatism as a mechanism of cultural and religious preservation?